2007
DOI: 10.1063/1.2799386
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Advanced Optical and Chemical Characterization Techniques for Optimization of High-κ Dielectrics with Nanometer Range Thickness

Abstract: Abstract.Complementary Metal Oxide Semiconductor (CMOS) down-scaling leads to a dramatic reduction of the gate dielectric thickness for the isolation efficiency. The properties of hafnium aluminium oxide (HfAlO) are investigated as an alternative to conventional Si02 as it exhibits the desirable characteristics of a high dielectric constant, a wide bandgap and good thermal stability with silicon. In this study, we show that complementary characterization techniques can be used to tune the deposition parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…This is in agreement with the data by Yu et al, 10 which showed that the gap energy of mixed layers determined via x-ray photoelectron spectroscopy changes linearly with the Hf fraction. A linear relationship was also observed by Licitra et al 11 employing SE in an energy range from 1.5 eV to 8.0 eV. In comparison with their results determined from the Tauc-Lorentz model, the optical constants determined here from the Gaussian dispersion model exhibit a better resolved line shape, which cannot be well described only by a Tauc-Lorentz contribution.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This is in agreement with the data by Yu et al, 10 which showed that the gap energy of mixed layers determined via x-ray photoelectron spectroscopy changes linearly with the Hf fraction. A linear relationship was also observed by Licitra et al 11 employing SE in an energy range from 1.5 eV to 8.0 eV. In comparison with their results determined from the Tauc-Lorentz model, the optical constants determined here from the Gaussian dispersion model exhibit a better resolved line shape, which cannot be well described only by a Tauc-Lorentz contribution.…”
Section: Resultssupporting
confidence: 77%
“…10,11,18 The Al 2 O 3 film reveals a gap of (6.71 6 0.02) eV, which is in the range of 6.4-7.1 eV observed for ALD films. 10,11,21 Looking at the optical gap of the Hf x Al y O z layers, it is clear that the gap position is linearly dependent on the Hf fraction (x) between pure HfO 2 film (6.71 eV) and pure Al 2 O 3 film (5.77 eV), as shown in Fig. 2(a).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…12 . 32,33 It can be noted that the values of ε r and n have been calculated to be (2.75, 1.66), (1.78, 1.33), (1.35, 1.16), (3.69, 1.92), (2.71, 1.65) and (1.78, 1.33), corresponding to samples S1–S6, respectively. The n values of S2, S3 and S5 deviate from the theoretical value of 2.1 and the experimental value of 1.6–1.9 in previous reports, 34,35 which means that only the current conduction mechanism (CCM) of the S1, S4 and S6 samples satisfies the SE mechanism at a lower electric field.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, based on the linear tting lines slope ¼ 1 kT can be extracted and are exhibited inFig. 12 32,33. It can be noted that the values of 3…”
mentioning
confidence: 99%